The Decline of Cash Assistance and the Well-Being of Poor Households with Children. (19th March 2019) - Shaefer, H Luke; Edin, Kathryn; Fusaro, Vincent; Wu, Pinghui
ABSTRACT: Since the early 1990s, the social safety net for families with children in the United States has undergone an epochal transformation. Aid to poor working families has become more generous. In contrast, assistance to the deeply poor has become less generous, and what remains more often takes the form of in-kind aid. A historical view finds that this dramatic change parallels others. For centuries, the nature and form of poor relief has been driven in part by shifting cultural notions of which social groups are "deserving" and "undeserving." This line was firmly redrawn in the 1990s. Did the re-institutionalization of these categorizations in policy have material consequences? This study examines the relationship between the decline of traditional cash welfare between 2001 and 2015 and two direct measures of wellbeing among households with children: household food insecurity and public school child homelessness. Using models that control for state and year trends, along with other factors, we find that the decline of cash assistance was associated with increases in both forms of hardship.